Educational Game for Learning Computational Thinking in a Low Budget Virtual Reality Environment - Sukirman Sukirman; Dias Aziz Pramudita; Abdylla Adhiyasa Nugroho; Muhammad Rizky Aminudin (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2023)
Virtual reality (VR) is a technology that can create a simulation of real objects in a virtual environment more interactively. In terms of budget, VR devices can be categorized into low budget and high end. However, both of them can still carry out the same interactive simulations, such as educational games. This research aims to develop an educational game based in low-budget VR environment for learning computational thinking (CT), one of the 21st century skills that students need to learn. The method used is Design and Development Research (DDR) that consists of five stages: analysis, design, development, testing, and evaluation. Participants involved in this study are 30 students of vocational school (SMK) majoring Computer and Network Engineering. Evaluation conducted through Technology Acceptance Model (TAM) framework that consists of perceived usefulness (PU), perceived ease of use (PEU), attitude toward using (ATU), and intention to use (ITU). Based on the data obtained and the analysis performed, the Cronbach’s alpha score of PU and PEU were 0.714 and 0.614, respectively. Meanwhile, the Cronbach’s alpha score of ATU and ITU were 0.754 and 0.882, respectively. PU and PEU are positively correlated with ATU, while ATU is also positively correlated with ITU. It means that the ease of use of the application and the usability aspects of the developed application have a positive effect on user attitudes. This positive behavior is also positively correlated with the intention to use it again on another occasion. Thus it can be concluded that this educational game based in low-budget VR environment can be used for learning CT. It can be seen from the analysis and some positive comments from students, like participants wish they can use this learning approach in the other subject.